Sterile cyst formation after intrathecal stem cell transplant for Parkinson's disease: A case presentation and literature review - Jaffar A. Al-Tawfiq; Ramzi W. Banda; Jihad Ghandour (Elsevier, 2015)
Summary: In recent years, fetal or autologous stem cell transplant for the treatment of Parkinson's disease (PD) has been practiced in a few medical organizations. However, the potential complications related to the growth of allograft tissue have not yet been well described apart from case reports. Here, we present a 42-year-old Saudi male who suffered from early onset Parkinson's disease. He sought medical care in China and received autologous intrathecal stem cell transplantation. He did not demonstrate any significant improvement. A few months later, the patient went back to China and underwent fetal cell transplantation into the left hemisphere and a second stem cell transplantation intrathecally. He presented with seizures and had a left frontal brain cyst. The cyst was drained and contained clear fluid. All cultures were negative. He had an uneventful recovery. Keywords: Brain abscess, Parkinsonism, Transplant, Brain cyst, Fetal stem cell